2009
DOI: 10.1038/aps.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

Different BAG-1 isoforms have distinct functions in modulating chemotherapeutic-induced apoptosis in breast cancer cells

Abstract: Aim: BAG-1 is a multifunctional anti-apoptotic gene with four isoforms, and different BAG-1 isoforms have different antiapoptotic functions. In this study, we transfected BAG-1 isoforms into the human breast cancer cell lines Hs578T (ER negative) and MCF-7 (ER positive) to study their effect on apoptosis with or without estrogens. Methods: The constructed recombinant expression vectors carrying individual BAG-1 isoforms was used to transfect human breast cancer cell lines Hs578T (ER negative) and MCF-7 (ER pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
14

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 22 publications
3
16
0
14
Order By: Relevance
“…We have previously used BAG-1 siRNA to downregulate the expression of BAG-1 in the human lung adenocarcinoma cell line A549, and found a significantly enhanced sensitivity to cisplatin-induced apoptosis in the BAG-1 siRAN transfected cells [30]. Similar observations were made in the MCF-7 breast cancer cells transfected with the BAG-1 siRNA and treated with doxorubin, docetaxel and 5-FU [24,31] and in the human cervical cancer cell lines treated with cisplatin staurosporine, paclitaxel and doxorubicine [23]. Our paradoxical finding of BAG-1 being a positive prognostic yet negative predictive biomarker in breast cancer is important clinically.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We have previously used BAG-1 siRNA to downregulate the expression of BAG-1 in the human lung adenocarcinoma cell line A549, and found a significantly enhanced sensitivity to cisplatin-induced apoptosis in the BAG-1 siRAN transfected cells [30]. Similar observations were made in the MCF-7 breast cancer cells transfected with the BAG-1 siRNA and treated with doxorubin, docetaxel and 5-FU [24,31] and in the human cervical cancer cell lines treated with cisplatin staurosporine, paclitaxel and doxorubicine [23]. Our paradoxical finding of BAG-1 being a positive prognostic yet negative predictive biomarker in breast cancer is important clinically.…”
Section: Discussionsupporting
confidence: 62%
“…Construction of plasmids containing the BAG-1 p50, p46, p33 was described previously [23,24], and all recombinant plasmids were confirmed by DNA sequencing. DNA transfection was performed using the Lipofactamine™ 2000 reagent (Invitrogen) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of Bcl-2 mRNA in leukemic patients using antisense technology resulted in increased apoptosis and potentiation of the effect of antineoplastic drugs in these patients [20]. Cell cycle arrest in G2/M or G0/G1 has been attributed to Bcl-2 [21].…”
Section: Introductionmentioning
confidence: 99%
“…4955 Furthermore, BAG1L and BAG1M overexpression have shown strong antiapoptotic and cell mitotic effects in cancerous cells, by activating BCL2 and RAF1. 56 It has been reported that BAG1 clients compete with each other to sequester BAG1 proteins. 48,49 Because BAG1 protein levels are much lower than its clients, a small change in BAG1 isoform expression, or that of HSP70, RAF1, and BCL2, could alter the interaction of BAG1 with GRα, RAF1, BCL2, or HSP70 and, subsequently, alter vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%